2013
DOI: 10.1002/rds.20012
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous propagation conditions observed over a tropical station using high‐resolution GPS radiosonde observations

Abstract: [1] A comprehensive study on the ducting conditions prevailing over the Indian tropical station of Gadanki (13.5 N, 79.2 E) is made using more than 5 years (April 2006 to September 2011) of high-resolution GPS radiosonde observations. In the present study, the characteristics of ducts occurring over Gadanki were examined statistically using the modified refractivity. Strong diurnal and seasonal variation in the percentage occurrence of the ducts was found with the highest and lowest occurrences during winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…By using the above equation, Basha et al . [] have calculated the minimum frequencies trapped during each month and found higher frequencies trapped during southwest monsoon season. However, in their report, note that wavelength (m) was mentioned on the y axis instead of frequency (GHz).…”
Section: Frequency Trappedmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the above equation, Basha et al . [] have calculated the minimum frequencies trapped during each month and found higher frequencies trapped during southwest monsoon season. However, in their report, note that wavelength (m) was mentioned on the y axis instead of frequency (GHz).…”
Section: Frequency Trappedmentioning
confidence: 99%
“…Numerous studies reported the seasonal and long‐term variation of various characteristics of atmospheric ducts like altitude, thickness, strength, and percentage of occurrence [ Brooks et al ., ; Haack and Burk , ; Von Engeln and Teixeira , ; Atkinson and Zhu , ; Mentes and Kaymaz , ; Ao , ; Basha et al ., ]. Especially, Von Engeln and Teixeira [] reported the diurnal variation of ducts over the globe using low vertical resolution European Centre for Medium‐Range Weather Forecasts (ECMWF) data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical studies of the occurrence of the atmospheric trapping layer in different regions have been carried out in the last few decades [7][8][9][10]. By using 6-year European Centre for Medium-Range Weather Forecasts (ECMWF) data, Engeln [8] calculated the atmospheric refractivity and analyzed the seasonal variations in the occurrence rate, altitude, thickness, and gradient of the trapping layer at a height of 0~2.5 km.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ducting layers do not have rigid boundaries, and some electromagnetic energy may leak out of the ducting layer [ Patterson et al ., ]. This effect is related to the strength of the duct, where stronger ducts trap more electromagnetic energy [ Basha et al ., ]. Identification/estimation of duct height, duct thickness, and duct strength from the M profiles for EM ducts are explained in the subsequent sections.…”
Section: Introductionmentioning
confidence: 99%